1983
DOI: 10.1159/000118012
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Withdrawal Symptoms with Delta Sleep-Inducing Peptide, a Neuropeptide with Potential Agonistic Activity on Opiate Receptors

Abstract: It has been postulated that delta sleep-inducing peptide (DSIP) possesses an agonistic activity on opiate receptors and might be of value in the treatment of withdrawal syndromes. To test this hypothesis, DSIP (25 nmol/kg) was injected intravenously as sole treatment to 67 patients presenting withdrawal symptoms (28 from ethyl alcohol, 39 from opiates). 27 % of the patients were lost or unsuitable for evaluation. From the 49 evaluable patients, DSIP produced a beneficial effect in 48 (22 alcoholics and 26 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…It does not necessarily correspond completely to the functions of endogenous DSIP at normal levels, nor does it limit the possible use fulness of DSIP in neurochemically abnormal conditions. Our above cited trial with 2 patients on benzodiazepine withdrawal yielded results comparable to observations in a clinical study with addicts [4], indicating that DSIP may be of value in withdrawal syndromes [54]. These and other possible clinical applications need further explora tion, whereas a revolutionary treatment for sleep distur bances seems to be near at hand.…”
Section: Synthesissupporting
confidence: 64%
“…It does not necessarily correspond completely to the functions of endogenous DSIP at normal levels, nor does it limit the possible use fulness of DSIP in neurochemically abnormal conditions. Our above cited trial with 2 patients on benzodiazepine withdrawal yielded results comparable to observations in a clinical study with addicts [4], indicating that DSIP may be of value in withdrawal syndromes [54]. These and other possible clinical applications need further explora tion, whereas a revolutionary treatment for sleep distur bances seems to be near at hand.…”
Section: Synthesissupporting
confidence: 64%
“…Administration of DSIP to rabbits [Monnier et al, 1977], rats [Kafi et al, 1979], cats [Pole et al, 1978], mice [Nagasaki et al, 1980] and humans [Schneider-Helmert et al, 1981a, b] confirmed the action of DSIP on sleep, monitored by electroencephalogram: the increase of sleep induced by DSIP is suppressed by the administration of the opiate antagonist Naloxone [Tissol, 1981], These studies show that DSIP, administered peripher ally, has a central action; the suggestion that this peptide crosses the blood-brain barrier has been experimentally confirmed [Kastin et al, 1981c;Banks ex al., 1982], Besides its effects on sleep, DSIP seems to interfere with such other homeostatic mechanisms as thermoregu lation [Yehuda and Kastin, 1980] and motor activity [Graf et al, 1981], The therapeutic use of DSIP in humans has shown promise for the treatment of insom nia [Schneider-Helmert et al, 1981a, b] and of the alco- hoi and opiate addiction withdrawal syndromes [Dick et al, 1982], However, the mechanism of action of DSIP is still unknown. Does it simply act upon endorphin recep tors, enkephalin receptors, etc., or are there specific DSIP systems in the brain?…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Finally, it has been postulated that DSIP modulates endogenous opioid-peptidergic systems and exogenous intracerebrally or systemically administered morphine. [13][14][15][16] Unfortunately, its mechanisms of action have never been fully determined. The objective of looking for a binding site for DSIP prompted us to investigate the synthesis of [ …”
Section: Introductionmentioning
confidence: 99%